Clonal dynamics of circulating tumor DNA during immune checkpoint blockade therapy for melanoma. Issue 11 (22nd September 2021) - Takai, Erina; Omata, Wataru; Totoki, Yasushi; Nakamura, Hiromi; Shiba, Satoshi; Takahashi, Akira; Namikawa, Kenjiro; Mori, Taisuke; Yamazaki, Naoya; Shibata, Tatsuhiro; Yachida, Shinichi
Abstract: Assessment of treatment efficacy of immune checkpoint inhibitors in melanoma patients is difficult as the response to these therapies varies among patients or lesions. The clonal evolution of cancer during immune checkpoint blockade therapy could cause treatment resistance. We investigated the potential of liquid biopsy in monitoring the mutational profiles of metastatic melanoma during immunotherapy. Plasma samples collected from 21 Japanese metastatic melanoma patients before immune checkpoint blockade therapy were subjected to whole‐exome sequencing (WES). Furthermore, 14 Japanese patients with melanoma were enrolled for longitudinal analysis of circulating tumor DNA (ctDNA). Plasma samples were collected prospectively before and during therapy and sequenced. WES of the pretreatment plasma from Japanese melanoma patients showed detectable ctDNA levels with wide ranges of variant allele frequencies within a sample, suggesting clonal and subclonal mutations in ctDNA. In targeted sequencing using longitudinal samples, ctDNA levels correlated with increased tumor size, while ctDNA content immediately decreased after a surge in a patient exhibiting pseudo‐progression, suggesting the potential of ctDNA analysis in discriminating between pseudo‐ and true progression. Mutant ctDNA levels showed different patterns within the clinical course of specific patients, suggesting that these mutations were derived from different tumor clones with distinct therapeutic responses. During further investigation, WES of plasma samples from 1 patient showed marked differences in the mutational profiles of ctDNA, including expansive tumor evolution during an acute exacerbation. Immunotherapy may induce characteristic clonal evolutions of tumors; longitudinal analysis of ctDNA has the potential of determining these tumor evolution patterns and therapeutic responses. Abstract : In this cohort of Japanese patients with metastatic melanoma, longitudinal analysis of ctDNA showed changes in the amounts of mutant DNA in plasma associated with clinical responses or pseudo‐progression, accompanied by altered mutational profiles of ctDNA during treatment with immune checkpoint inhibitors. Longitudinal evaluation of ctDNA may potentially predict the response to treatment and elucidate clonal evolution of melanoma during immunotherapy.